2010
DOI: 10.1111/j.1099-0860.2010.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of Young Men and Their Teenage Partners on Maternity and Health Services During Pregnancy and Early Parenthood

Abstract: This study discusses young couples’ interactions with maternity and health services paying particular attention to men’s perspectives. Findings are based on research conducted in Scotland with men (aged 16–25) and their teenage partners (aged 16–19). Most young men were very involved in their child’s life and provided support and care to their partner during pregnancy and in early parenthood. Men often felt excluded or judged when accessing services, although positive experiences were reported too. The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…Interestingly, this may be in contrast to the experience of fathers, especially marginalized young or black fathers (Ross et al . ). In a review of existing qualitative research in this area, Steen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, this may be in contrast to the experience of fathers, especially marginalized young or black fathers (Ross et al . ). In a review of existing qualitative research in this area, Steen et al .…”
Section: Discussionmentioning
confidence: 97%
“…The authors of this article acknowledge that there could be different ways people may prepare for parenthood; however, much more information appears to be available for high-risk or problematic groups (Moriarty Daley, Sadler, & Dawn Reynolds, 2013;Ross, Church, Hill, Seaman, & Roberts, 2012). Preparation may be different with those planning first-time parenthood from those experiencing subsequent parenthood.…”
Section: Introductionmentioning
confidence: 83%
“…When accessing health and maternity services, experiences of feeling excluded and marginalised were frequently reported by the young fathers in Ross et al's (2012) study along with reports that antenatal classes were an intimidating environment because of the presence of older couples. These issues are of concern because research evidence shows a clear need to better involve young fathers in support services, because doing so has a range of benefits both for themselves and for the well-being of their children (Deslauriers et al, 2012).…”
Section: Are Young Dads Hard To Reach?mentioning
confidence: 96%
“…For very young fathers, a lack of awareness of what services might be available to them may be compounded by a lack of confidence or ability to find appropriate support if they are kept distant from their child by difficulties in family relationships. Ross et al's (2012) study of young parents' engagements with healthcare services found that they were particularly sensitive to how they were treated by staff when accessing services because they were aware of the negative stereotypes that were attached to them because of their youth. In a study of young fathers' experiences of the Family Nurse Partnership, Ferguson (2016) identified that their non-engagement arose from a combination of service delivery issues that made engagement difficult, and from some complex issues around their own vulnerabilities and prior negative experiences as service users "the hostility of men who won't engage arises partly from the nature of the service and the ways it is delivered and also seems to come from their deep experience of social suffering and pained defensiveness that makes isolation and being unreachable highly attractive."…”
Section: Are Young Dads Hard To Reach?mentioning
confidence: 99%